PENDIDIKAN ISLAM DI ANDALUSIA - Meifa Adinda Erwina; Muhammad Zalnur; Fauza Masyhudi (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to examine the development of Islamic education in Andalusia as part of the dynamics of Islamic civilization. This study uses a library research method with a historical approach to understand educational phenomena during the period of Islamic rule in Spain (711–1492 AD). The main focus of research is on educational institutions such as kuttabs and universities, the development of science, and factors supporting educational progress. The research results show that Islamic education in Andalusia does not only involve religious knowledge, but also the fields of philosophy, medicine, science, art and language. Educational institutions such as the kuttab taught the basics of jurisprudence, language and art, while universities such as the Universities of Cordova and Granada became scientific centers that produced famous scientists such as Ibn Hazm and Ibn Rushd. Internal factors such as Islamic values ​​and motivation to study, as well as external factors in the form of support from authorities and intellectual competition with the Eastern Islamic world, are the main drivers of this progress.